The evaluation of internal adaptation of glass ionomer restorations applied after the use of different cavity conditioners in primary teeth: an in-vitro study - Sümeyye Gürler; Akif Demirel; Arda Buyuksungur (BMC Oral Health)
Abstract Background This study aimed to comparatively evaluate the effects of different cavity conditioners on internal adaptation (IA) of glass ionomer-based restorative materials applied to primary teeth. Methods 80 extracted primary second molar teeth were randomly assigned to four different cavity conditioner groups [10% polyacrylic acid, 20% polyacrylic acid, 17% ethylene diamine tetraacetic acid (EDTA), 35% phosphoric acid]. Class V cavities were prepared on the buccal surfaces and relevant cavity conditioners were applied, and the samples in each cavity conditioner group were randomly assigned to glass hybrid (GHR) or conventional glass ionomer restoratives (CGIR). Subsequently, restorative materials were applied and all samples were thermocycled (5–55 °C, 5000 cycles) and IA were calculated volumetrically by using a Micro Computed Tomography (Micro-CT) system. IA values was recorded as % and data were analyzed with Mann-Whitney U and Kruskal-Wallis H tests. Statistical significance level was set as 5%. Results 35% phosphoric acid showed the lowest mean internal voids (between the cavity-restoration interface) for both restorative materials (for GHR = 0.180% and for CGIR = 0.936%). However, the highest mean internal voids for GHR and CGIR were observed after the use of 17% EDTA (2.438%) and 10% polyacrylic acid (8.483%), respectively. For both restorative materials, 20% polyacrylic acid showed the second lowest mean internal voids (for GHR = 0.321% and for CGIR = 3.580%), however, no significant difference was found between 35% phosphoric acid and 20% polyacrylic acid (p = 0.941 for GHR and p = 0.061 for CGIR). In the samples applied the cavity conditioners other than 17% EDTA, glass hybrid restoratives showed significantly higher IA quality than conventional glass ionomer (p = 0.0001 for 10% polyacrylic acid, p = 0.001 for 20% polyacrylic acid and p = 0.002 for 35% phosphoric acid). Conclusions Within the limitations of this study, 35% phosphoric acid and 20% polyacrylic acid were determined to be the most successful cavity conditioners in terms of IA, and glass hybrid restorative system showed superior IA quality than conventional glass ionomer. Further studies are needed to confirm the present results.